La construcción de una mirada: el desarrollo del campo de la fotografía peruana a la luz de la estética de la Escuela de Dusseldorf - Hernández Kcomt, Hernán Juan Pablo (2024)
This research focuses on the emergence and institutional consolidation of a photographic aesthetic in Peru that, at the time, was understood by various actors in the field as being related to that of the Düsseldorf School. Through an analysis of certain works by Peruvian photographers (Flavia Gandolfo, Roberto Huarcaya, Luz María Bedoya, Juan Enrique Bedoya, Philippe Gruenberg, Edi Hirose, Solange Adum, Andrés Marroquin, and Marco Garro) and their relationship with the aesthetic principles of the German school, the interaction between artists, institutional agents, and the local art market is examined. The methodology is divided into three chapters: one focused on elucidating the formal characteristics of the Düsseldorf School, another contextualizing the Peruvian photographic panorama during the 1990s and the early 2000s, and a third conducting a comparative analysis of these works, also relying on interviews to understand their valuation in the cultural and economic context. In this sense, the aim is to analyze the role of curators, collectors, and especially the Centro de la Imagen, as a convergence of formative and market axes, in the validation of this aesthetic. Thus, the works are examined in light of a chronology organized from a period of independent production in the second half of the 1990s, through a period of institutional consolidation in the first decade of the 2000s, until reaching a maturity of the field defined by the fairs and biennials that took place in the 2010s.